2008
DOI: 10.1590/s1413-86702008000600008
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ cell counts in patients with different clinical manifestations of tuberculosis

Abstract: Tuberculosis is the prototype of infections that require a cellular immune response for their control. It has been shown that CD4+ T-lymphocytes are most important in the protective response against Mycobacterium tuberculosis. CD8+ T-lymphocytes are also important for effective T-cell immune response. This study compares CD4+ and CD8+ baseline values in patients with different manifestations of tuberculosis. CD4+ and CD8+ in three groups of patients with tuberculosis (pulmonary, lymphadenitis, meningitis/milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 14 publications
5
29
0
1
Order By: Relevance
“…In a study by Han Pin Kuo et al, in the BAL of HIV negative TB patients, they observed significant increase in the CD4:CD8 ratio with respect to normal subjects (2.8±0.4 versus 1.3±0.2, p=0.03) which was similar to results reported by Singhal et al 17,18 This finding is contrary to that observed by Ashtekar MD et al, Uppal et al and Davoudi et al, who reported significant reduction of the CD4:CD8 ratio which can be due to CD8 lymphocytosis with CD4 lymphopenia. 6,13,19 …”
Section: Discussionmentioning
confidence: 99%
“…In a study by Han Pin Kuo et al, in the BAL of HIV negative TB patients, they observed significant increase in the CD4:CD8 ratio with respect to normal subjects (2.8±0.4 versus 1.3±0.2, p=0.03) which was similar to results reported by Singhal et al 17,18 This finding is contrary to that observed by Ashtekar MD et al, Uppal et al and Davoudi et al, who reported significant reduction of the CD4:CD8 ratio which can be due to CD8 lymphocytosis with CD4 lymphopenia. 6,13,19 …”
Section: Discussionmentioning
confidence: 99%
“…7 After performing additional literature review, milliary tuberculosis (TB) was also added to the immunosuppressive conditions, as it has been associated with T cell deficiency. 8 DCHZ was defined as >20 skin lesions beyond the primary or adjacent dermatomes. 9 Sixteen related publications were identified.…”
Section: Discussionmentioning
confidence: 99%
“…The CD4 count in our case was less than normal (500–1500 cells/mm 3 ) but it did not fulfil the criteria for CD4 lymphopenia. The explanation for this may be that TB itself may lead to low CD4 count as has been shown in previous studies 11. We could not investigate for the interferon gamma and interleukin 12 pathway which when deficient or ineffective may lead to MSMD.…”
Section: Discussionmentioning
confidence: 80%